Common proverbs and sayings in Kazakh and Turkish languages - Nazarova А Zh; Saduova Sh М (Journal of Oriental Studies, 2016)
In this article common proverbs in Kazakh and Turkish languages are examined and compared. During the comparative research work we used Kazakh-Turkish dictionaries of proverbs and sayings. Likeness of the proverbs of these languages is given as an example in this article. As a result of research it was noticed that in two languages it is possible to find an equivalent to the proverbs, but also there are proverbs without analogues. These features in languages show the close connection Turkic people during the long time.